Pengetahuan Ibu Tentang Kejadian Ikutan Pasca Imunisasi (KIPI) pada Bayi 0-12 Bulan Di Posyandu Desa Tanah Datar Kecamatan Rengat Barat - Isnaniar; Nolita, Wiwik; Silvia, Mega (As-Shiha: Jurnal Kesehatan, 2023)
Vaccines do not cause reactions in the body, if they occur they cause mild reactions. The reaction after this vaccine is called Post-Immunization Follow-up Event (AEFI) which can have a negative impact if the mother lacks knowledge for proper treatment. Objective: To find out the description of mother's knowledge about AEFI who have babies in Tanah Datar Village who have received basic immunization. This type of research is descriptive with prospective data collection. The population is all infants who received immunization in May-July 2023 as many as 40 people. The sampling technique used was a purposive sampling method with a total of 25 respondents. Data analysis in this scientific paper was carried out univariately in the form of presenting a frequency distribution table. Instrument this scientific writing uses a questionnaire given and filled in by the respondent. The results of scientific writing what has been done by the researchers is that the mother's knowledge about follow-up events after basic immunization in infants, at the Tanah Datar Village Posyandu in 2023 is in the pretty good category as many as 18 respondents (45%), both 10 respondents (25%) and unfavorable category 12 respondents (30%). Conclusion it is hoped that Posyandu as a health service facility can determine promotive and preventive steps to increase public awareness of infant health